Profiling charge transport: A new computational approach - Maqboul, Ibrahim (International Journal of Biological Macromolecules, 2023)
To maintain life, charge transfer processes must be efficient to allow electrons to migrate across distances as large as 30–50 Å within a timescale from picoseconds to milliseconds, and the free-energy cost should not exceed one electron volt. By employing local ionization and local affinity energies, we calculated the pathway for electron and electron-hole transport, respectively. The pathway is then used to calculate both the driving force and the activation energy. The electronic coupling is calculated using configuration interaction procedure. When the charge acceptor is not known, as in oxidative stress, the charge transport terminals are found using Monte-Carlo simulation. These parameters were used to calculate the rate described by Marcus theory. Our approach has been elaborately explained using the famous androstane example and then applied to two proteins: electron transport in azurin protein and hole-hopping migration route from the heme center of cytochrome c peroxidase to its surface. This model gives an effective method to calculate the charge transport pathway and the free-energy profile within 0.1 eV from the experimental measurements and electronic coupling within 3 meV.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Androstane; Azurin; Cytochrome C peroxidase; Dijkstra algorithm; Electron transport; Hole-hopping; Ionization; Metropolis Monte-Carlo